STRATEGI PENINGKATAN PARTISIPASI PEMUDA DALAM KEGIATAN MASJID MELALUI PROGRAM KKN DI MASJID TAQWA DESA TUMBUAN - Ferdiansyah, Rahman Dwi; Melati , Rima; Oktania , Veby; Khoirunnisa , Wahdah; Anggela, Feby; Lestari , Onesa; Sustiawan , Egi; Hidayati , Salma; Anggela , Rasta Fabi; Anggraini , Zeta (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Youth participation in mosque activities in Tumbuan Village, Seluma Regency, has decreased in recent years. To overcome this problem, the mosque-based Real Work Lecture Program (KKN) at the FAS State Islamic University (UIN FAS) was introduced as a strategy to increase youth participation. This research aims to evaluate the effectiveness of the program in increasing youth involvement in mosque activities. The research method used is a qualitative approach with in-depth interview techniques, observation and document analysis. The research results show that the mosque-based KKN program has succeeded in increasing youth participation significantly through activities that involve youth in planning and implementing the program. In addition, youth have become more aware of the importance of their role in maintaining the sustainability of mosque activities. This program also faces several challenges, such as limited resources and support from the community. In conclusion, service-learning-based strategies that involve youth in mosque activities have great potential to increase participation, although further efforts are needed to overcome existing challenges.